Challenges with participant reimbursement: experiences from a post-trial access study - Mngadi, Kathryn Therese; Frohlich, Janet; Montague, Carl; Singh, Jerome; Nkomonde, Nelisiwe; Mvandaba, Nomzamo; Ntombeka, Fanelesibonge; Luthuli, Londiwe; Abdool Karim, Quarraisha; Mansoor, Leila (Journal of medical ethics, 2015)
Reimbursement of trial participants remains a frequently debated issue, with specific guidance lacking. Trials combining post-trial access and implementation science may necessitate new strategies and models. CAPRISA 008, a post-trial access study testing the feasibility of using family planning services to rollout a prelicensure HIV prevention intervention, tried to balance the real-life scenario of no reimbursement for attendance at public sector clinics with that of a trial including some visits that focused on research procedures and others that focused on standard of care procedures. A reduced reimbursement was offered for ‘standard of care’ visits, meant primarily to cover transport costs to and from the clinic only. This impacted negatively on accrual, retention and participant morale, primarily due to the protracted delay in regulatory approval, during which time, the costs of living, including travel costs had increased. Relevant guidelines were reviewed and institutional policy was updated to incorporate the South African National Health Research Ethics Committee guidelines on reimbursement (taking into account participant time, travel and inconvenience). The reimbursement amount for ‘standard of care’ visits was increased accordingly. The question remains whether a trial that combines post-trial access with implementation science, with clear benefits for the participants and the provision of above standard medical care, should have reimbursement rates that approach those of a proof-of-concept trial, for ‘standard of care’ visits.